Integrating Javanese Culture into English Pronunciation and Vocabularies Learning at SDN Gading Surakarta - Donie Fadjar Kurniawan; Mohammad Ubaidul Izza; Meutia Rafa Anandita (Indonesia Berdaya, 2026)
This community service is in the form of a spoken English workshop for beginners through the introduction and improvement of correct pronunciation skills and sufficient vocabulary. This is deemed necessary because it is a needed foundation whether the spoken English is correct or not and its use in the next stage. The method is descriptive qualitative design within a community service framework. The participants of this learning workshop are students of grades 4, 5, 6 of State Elementary School (SDN) Gading Surakarta with a composition of 10 students each with the school conducting the selection. The training time is July to August 2025. The teaching materials were developed based on the principles of contextual teaching and learning (Johnson, 2002), in which English such as number, color, simple phrase are introduced through familiar cultural content such as wayang, gamelan, batik, keris, joglo and various Javanese culture. The result of this training is that spoken English has been known and practiced by participating students. From the number 0 /ˈzɪəroʊ / to 100 /wʌn ˈhʌndrəd/;  colors and simple phrase such as white joglo (/waɪtjoglo/). This training also successfully integrated the Javanese culture into spoken English learning through pronunciation and vocabulary can significantly improve student engagement and understanding.